IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT AND SERVICE QUALITY TO CUSTOMER LOYALTY SHOWROOM "MUJUR MOBIL" - Sandra Oktaviana Pinaraswati; Saibat Saibat; Agustiawan Djoko Baruno; Suprihati Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to examine and prove the effect of the implementation of Customer Relationship Management and service quality on customer loyalty at Showroom “Mujur Mobil”. This study aims to determine customer factors in an effort to increase customer loyalty which is very useful, especially for business people in offering services. This study uses a quantitative approach with multiple linear regression analysis. The number of samples taken was 50 respondents and data collection was carried out by questionnaires to obtain data. The results of this study are customer relationship management (CRM) partially has a significant positive effect on customer loyalty, while service quality partially has a significant positive effect on customer loyalty, and simultaneously CRM and service quality have a positive impact on customer loyalty. Keywords : Customer Relationship Management, Service Quality, Customer Loyalty.